Model jurysdykcji sądowej w postępowaniu sądowoadministracyjnym a konstytucyjne funkcje sądów administracyjnych - Gębala, Katarzyna (My University, 2016)
Przedmiotem dysertacji jest zagadnienie modelu jurysdykcji sądowej w postępowaniu sądowoadministracyjnym w kontekście konstytucyjnych funkcji sądów administracyjnych. Ukształtowany przez ustawodawcę model jurysdykcji sądowej w postępowaniu sądowoadministracyjnym ma co do zasady charakter kasacyjny. Kasacyjny model jurysdykcji sądowej w postępowaniu sądowoadministracyjnym może budzić wątpliwości nie tylko z punktu widzenia efektywności ochrony sądowej, ale przede wszystkim z punktu widzenia wypełniania powierzonej w Konstytucji RP sądom w tym sądom administracyjnym funkcji polegającej na sprawowaniu wymiaru sprawiedliwości, a która jest integralnie powiązana z zagwarantowanym prawem do sądu. Głównym problemem badawczym jest udzielenie odpowiedzi na pytanie, czy obowiązujący model jurysdykcji sądowej w postępowaniu sądowoadministracyjnym zapewnia realizację przez sądy administracyjne powierzonych im przez ustrojodawcę funkcji oraz czy gwarantuje on rzeczywistą ochronę praw jednostki w sferze prawa administracyjnego. Dysertacja obejmuje cztery rozdziały. Rozdział I dotyczy zagadnień podstawowych i tła historycznego. Rozdział II poświęcony został zagadnieniu konstytucyjnych i konwencyjnych uwarunkowań modelu jurysdykcji sądowej w postępowaniu sądowoadministracyjnym. W rozdziale III przedstawiony został model jurysdykcji sądowej w postępowaniu sądowoadministracyjnym na tle rozwiązań ustawowych. Za przedmiot rozważań rozdziału IV przyjęto model jurysdykcji sądowej w postępowaniu sądowoadministracyjnym w systemie prawa niemieckiego.

The subject of the dissertation is the issue of a model of judicial jurisdiction in judicial administrative proceedings in the context of constitutional functions of administrative courts. The model of judicial jurisdiction in judicial administrative proceedings formed by the lawmaker is in principle the nature of cassation. The cassation model of judicial jurisdiction in judicial administrative proceedings may rise concerns not only from the point of view of the effectiveness of judicial protection, but above all from the point of view to fulfill the function of justice assigned to the courts including the administrative courts in the Constitution of the Republic of Poland which is integrally linked to guaranteed by the law - the right to a court. The main research issue is to answer the question of whether the binding model of judicial jurisdiction in judicial administrative proceedings ensures the implementation of the functions assigned by the lawmaker to the administrative courts and whether it ensures the effective protection of individual rights in the sphere of administrative law. The dissertation consists of four chapters. The first chapter concerns the essential issues and historical background. The second chapter concerns the issue of the conditions by the Constitution and the conventions of the model of judicial jurisdiction in judicial administrative proceedings. The third chapter presents the model of judicial jurisdiction in judicial administrative proceedings on the background of legislative solutions. As a matter of consideration of the fourth chapter was adopted the model of judicial jurisdiction in judicial administrative proceedings in the German legal system.
Model of judicial jurisdiction in judicial administrative proceedings and constitutional functions of administrative courts
Wydział Prawa i Administracji: Katedra Prawa Konstytucyjnego
Keywords: wymiar sprawiedliwości; prawo do sądu; sądy administracyjne; jurysdykcja sądowa; justice; right to a court; administrative courts; judicial jurisdiction